Evaluación de factores de riesgos psicosociales y la incidencia en la salud de los servidores y trabajadores del gobierno autónomo descentralizado del cantón Pujilí 2015 - 2016. Elaboración de un instructivo para la prevención de riesgos psicosociales. - Iza Cando, Hugo Fernando (2017)
In the present study, the psychosocial risk factors and the health impact of GAD servers and workers of Pujilí were evaluated for the elaboration of an user´s manual for the prevention of psychosocial risks. At the beginning, it was determined the application of FPsico-3.1 method, to evaluate the psychosocial risk factors in the Administrative area and also in the Operational area. As a result of this work, the method, techniques and programs that help the Institution to know, evaluate and act about psychosocial risks , analyzing the relationship that this risk factor has with the health condition of the employees and workers, managing the control measures according to the intervention levels; individual level for specific cases identified that require a special follow-up, organizational level, involving all the servers, workers and authorities of GAD in Pujilí, in each of the psychosocial dimensions. Finally, we can conclude that within the institution there are psychosocial risks that are affecting the mental health of employees and workers who are between 35 and 54 years of age; as a result it is necessary to develop prevention plans and programs.